Impact of Urban Cooling Island on Land Surface Temperature Change in Chattogram City - Chowdhury, Moumita; Sultana, Naznin Nahar; Sultana, Taj; Paul, Alak (Chittagong University Journal of Biological Sciences, 2025)
The study aims to identify the changing thermal behavior of the Chattogram City Corporation area by assessing the influence of the UCI's effect on Land Surface Temperature (LST). To achieve this purpose, Landsat L1TP satellite images have been geometrically and topographically corrected, and Normalized Difference Vegetation Index (NDVI), Normalized Difference Water Index (NDWI), and LST have been calculated. The study reveals the changing conditions of urban cooling islands and their relation to the spatial and temporal variation of thermal behavior within the city. As the cooling areas declined over time and the LST gradually increased, rising from a maximum of 25 degrees Celsius in 1989 to 34 degrees Celsius in 2019. The results of the study can be an effective direction for land use planning and sustainable urban development by considering UCIs to mitigate severe thermal impacts and adapt to urban microclimate change. Chittagong Univ. J. B. Sci. Vol. 13 (1&2): 46-59, 2025